Algebraic Question Types in Grade 10 Mathematics Textbook: A Cognitive Perspective - Sibiya, Mandlenkosi Richard; Sekao, David; Ogbonnaya, Ugorji (CV Sinergi Ilmu dan Publikasi, 2025)
Mathematics education depends on textbooks as the primary source of information for both teachers and learners while providing essential tasks that develop cognitive skills. The types of tasks used in these resources directly affect learners’ cognitive growth and show why textbooks must contain various question types. Current research lacks examination of mathematics textbooks in South African schools, even though learners consistently perform poorly in mathematics. This study investigated whether a widely used Grade 10 Mathematics textbook challenged learners to various question types that help build problem-solving skills and high-level thinking. A deductive content analysis approach evaluated 1 360 questions from the textbook’s algebra content, including algebraic expressions, exponents, equations and inequalities, number patterns, and functions. The research results indicated that most questions (62%) required routine calculations while the content lacked questions that required higher-order cognitive skills such as problem-solving, argumentation and interpretation. The assessed textbook appears to fail learners by not adequately developing critical thinking skills that learners need for both future advanced math classes and practical applications. The study recommends more diverse question types in mathematics textbooks to develop learners’ cognitive skills and problem-solving abilities.